Solvents extraction effects on bioactive compounds of ajwa date (Phoenix Dactylifera L.) flesh using mixture design - Elma S.N.; Badarusham K.; Salvamani S.; Hassan M.S.; Hashim R.; Dzulfadli Rosli (Italian Association of Chemical Engineering - AIDIC, 2024)
Indexed by SCOPUS